«Bless yourself included in Union new monasticism...» Letters of Metropolitan Anthony (Khrapovitsky) to Bishop Boris (Plotnikov) (1886–1900 biennium) - Sukhova Nataliia (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication presents the letters of Metropolitan Anthony (Khrapovitsky), one of the most famous bishops of the Russian Orthodox Church the late XIX — early XX century. The letters belong to the early period of the educational and church activities of Metropolitan Anthony (1886–1900). The letters addressed to archimandrite, and on March 1886 Bishop Boris (Plotnikov) — graduate and teacher of the Kazan Theological Academy, and then inspector of the Moscow Theological Academy, rector of the Kiev Theological Seminary and Saint Petersburg Theological Academy. The author of the letters regards the problems of academic monasticism in Russia, theological schools and the general condition of the spiritual life of Russian society 1880–1890-ies. So, Metropolitan Anthony formulates their concept of education of the priesthood and the consolidation of academic monasticism, which, from the point of view of Metropolitan Anthony, must play a crucial role in solving spiritual problems of Russian society. There have been some important features of the spiritual life of the school in one of the most diﬃcult periods of their history. Published letters are in the archive fund bishop Boris (Plotnikov) in the Department of Manuscripts of the National Library of Russia, and researchers have not been used previously.